The Effect of Leverage, Risk Management Committee, and Earnings Persistence on Real Earnings Management - Gunawan Gunawan; Januar Eko Prasetio (AIBPM Publisher, 2025)
The banking industry is inherently vulnerable to financial manipulation due to its high leverage structure, complex transactions, and direct access to liquid financial assets. Profit management can be viewed as the right of managers to establish certain accounting policies from an academic perspective; however, it is often viewed as fraudulent behavior by practitioners. This study aims to examine how leverage, the risk management committee (RMC), and earnings persistence affect real earnings management (REM). Using a quantitative approach and purposive sampling, the study analyzes 47 banking companies, resulting in 198 usable observations after outlier removal. The results show that leverage and the risk management committee have a significant effect on real earnings management, with significance values of 0.014 ( 0.05) and 0.042 ( 0.05), respectively, while earnings persistence (sig. = 0.186) does not have a significant effect. Simultaneous testing also confirms a significant joint influence (sig. = 0.008), although the adjusted R-squared value is only 0.044 (4.4%), indicating that the independent variables collectively explain a limited portion of real earnings management. Future research is recommended to incorporate additional independent variables to better explain real earnings management.